(untitled) (African Journal of Biomedical Research, 2024)
Microbial infections are very common in developing countries like Nigeria. It is the cause of poverty as well as many deaths in developing countries, while the current treatments are encountering resistance by these pathogens. However, natural products can help to overcome the problems associated with pathogenic diseases. Ethanolic extract of Ficus sycomorus stem bark was evaluated phytochemically for its constituents and antimicrobial potential on selected Gram-positive and Gram-negative organisms. The extract was fractionated by column and pooled into four fractions (A–D), these were evaluated for their antimicrobial activity against E. coli, S. typhi, S. aureus and K. pneumonia at different concentrations. The fractions A–C were active at concentration of 50-100 mg/mL. Ficus sycomorus was phytochemically and biologically explored for its antimicrobial potential against some selected organisms. The low MIC values of the crude extract against S. aureus and K. pneumonia holds potential for use as antimicrobial drug leads.